2015
DOI: 10.1049/el.2014.3845
|View full text |Cite
|
Sign up to set email alerts
|

Boost bulk‐driven sense‐amplifier flip‐flop operating in ultra‐wide voltage range

Abstract: A new boost bulk-driven sense-amplifier-based flip-flop (BBDSAFF) is presented. First, thanks to the boost and bulk-driven technique, the BBDSAFF consumes much lower power and can operate normally in the ultra-wide voltage range. Secondly, the adopted pseudo-PMOS dynamic technique in the RS latch output stage can greatly reduce the delay and improve the driving capability. The simulation results show advantages of high-speed, low power dissipation and very small and symmetrical rise/fall delay. Under the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The asymmetrical C-Q of conventional SAFF was overcome in Nikolic SAFF [5] and Strollo SAFF [6] by utilising a symmetrical slave latch. There are also other recently proposed improved SAFF topologies namely boost-bulk SAFF (BB-SAFF) [7] and transition completion detection SAFF (TCD-SAFF) [8]. Nevertheless, all these SAFF topologies still suffer from poor driving capability at ultra-low supply voltages leading to speed degradation and poor PDP performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The asymmetrical C-Q of conventional SAFF was overcome in Nikolic SAFF [5] and Strollo SAFF [6] by utilising a symmetrical slave latch. There are also other recently proposed improved SAFF topologies namely boost-bulk SAFF (BB-SAFF) [7] and transition completion detection SAFF (TCD-SAFF) [8]. Nevertheless, all these SAFF topologies still suffer from poor driving capability at ultra-low supply voltages leading to speed degradation and poor PDP performance.…”
mentioning
confidence: 99%
“…Simulation results: The proposed CB-SAFF has been designed in 40 nm CMOS along with the conventional SAFF [4], Nikolic SAFF [5], recently proposed BB-SAFF [7] and TCD-SAFF [8] for evaluation of performance metrics in same environment. All SAFFs are individually optimised, use same size input/output transistors and load capacitance of 15 fF for fair comparison.…”
mentioning
confidence: 99%
“…The proposed capacitively boosted SAFF is designed using 40 nm / 1.1 V CMOS technology. Other SAFF topologies such as the recently published BB-SAFF [39] and TCD-SAFF [40], Nikolic SAFF [37] and conventional SAFF [36] are also designed in 40 From the simulation results, it can be observed that the proposed CB-SAFF achieves the lowest power-delay product among all the other SAFF topologies for a VDD of 0.16 V to 0.6 V. The proposed FF is also the only flip-flop which can work at a VDD of 0.16 V at a CLK of 1 MHz as shown in Figure 3.3. The supply voltage is kept below 0.7 V, to prevent the parasitic junction diodes from forward biasing which will increase the overall power consumption.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Another SAFF topology which achieved low propagation delay than [28] also suffered from larger asymmetrical delays at ultra-low supply voltages due to poor drive strength [38] as shown in Figure 2.6. Recently, other improved performance SAFF topologies such as the boost-bulk SAFF (BBSAFF) [39] as shown in Figure 2.7 and the transition completion detection SAFF (TCD-SAFF) [40] as shown in Figure 2.8 were proposed and they also suffer from larger asymmetrical delays due to a greater imbalance between their output charging and discharging paths.…”
Section: Figure 25 -Nikolic Saff [37]mentioning
confidence: 99%